Synthesised innovation drivers and barriers in the energy sector - Faerber, Laura Antonia; Balta-Ozkan, Nazmiye; Ünal, Enes (Elsevier, 2026)
In a structured literature review, this study unifies the fragmented body of literature on drivers and barriers to innovation in the energy sector. A total of 273 publications were screened for relevance. 64 met the predefined criteria and were included in the dataset. The study makes unique contributions by developing the intersections of the drivers and barriers in four domains: energy companies can influence (1) the curse of incumbency on innovation and (2) the importance of economic performance and value creation of innovation, whereas policymakers have a strong lever on (3) the dual role of regulation and policy for innovation and (4) the effects of market dynamics on innovation. Moreover, the study reveals an imbalance in the research focus on innovation in the energy sector, with more studies addressing innovation drivers than barriers, which introduces an optimistic narrative. Most identified innovation drivers represent ideal conditions or market conditions beyond the energy sector. In contrast, the innovation barriers offer concrete constraints hindering innovation that can be directly addressed in the energy sector. Therefore, policymakers should emphasise solving embedded problems over promoting non-energy sector-specific enablers. This translates to innovation-friendly policy and regulation considering that energy companies need to simultaneously (1) address high investment costs by forming partnerships with non-energy sector companies, (2) accept the different risk profile of innovation compared to existing products, (3) equip their workforce with the knowledge and skill set to innovate and (4) adapt standards and processes instituted over decades to innovation.
Keywords: 33 Built Environment and Design; 4802 Environmental and Resources Law; 44 Human Society; 48 Law and Legal Studies; 4407 Policy and Administration; 3304 Urban and Regional Planning; 7 Affordable and Clean Energy; 9 Industry, Innovation and Infrastructure; Energy